Pengaruh Dukungan Sosial dan Self Esteem terhadap Motivasi Kerja pada Mahasiswa yang Sudah Bekerja - Syahdad Faturrohman; Fardan Afif; Elthon Muhammad Ray Alexis; Lucky Purwantini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to analyze the effect of social support and self esteem on work motivation in working students. The research method used in this study is quantitative with a correlational design used to examine the relationship between social support variables and self esteem to work motivation with the sampling technique used, namely purposive sampling. Data collection in this study is using a social support scale, self esteem scale, and work motivation scale on 134 students who have worked with a length of work <1 year - >4 years. The analysis techniques used in this study are spearmen correlation and multiple linear regression. The results of the analysis that has been done show that there is a significant positive relationship in social support to work motivation. These results indicate that students who are already working and have high social support will increase their work motivation. However, self esteem shows that there is no significant influence on work motivation. In this study, the effective contribution value given from each variable is r2 = 0, 658 or 65.8%.